Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J.; Platas, G.; Pelaez, F. (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
The following values have no corresponding Zotero field: pub-location: PUBLICATIONS DEPT, BRONX, NY 10458 USA publisher: NEW YORK BOTANICAL GARDEN
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae

Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J; Platas, G; Pelaez, F (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae

Effects of three fungal pathogens on water relations, chlorophyll fluorescence and growth of Quercus suber L - Luque, Jordi; Cohen, Moshe; Save, Robert; Biel, Carmen; Álvarez F., Isabel (Ann. For. Sci., 1999)
Some physiological and growth parameters were studied in cork oak plants inoculated with three pathogenic fungi growth, stomatal conductance, air-leaf temperature and photo- (Botryosphaeria stevensii, Hypoxylon mediterraneum and Phytophthora cinnamomi) in order to understand the effects of the fungal infection. All inoculated fungi induced the reduction of daily stem chemical efficiency. The more aggressive pathogens, B. stevensii ans P. cinnamomi, induced the sharpest decline in all growth and physiological parameters. A sudden decline of all variables was caused by B. stevensii within 6 days after inoculation, followed by a temporary increase in maximum daily shrinkage coinciding with wilting of the plants. The plants inoculated with P. cinnamomi underwent a more gradual decrease in all parameters, whereas H. mediterraneum induced a slight but still significant reduction only in stem growth and shrinkage. Linear variable displacement transducers (LVDT) proved to be a suitable tool to measure some effects of the pathogenesis.
Keywords: Botryosphaeria stevensii; hydric stress; Hypoxylon mediterraneum; LVDT; pathogenic effect; phytophthora cinnamomi

Micoflora asociada al alcornoque - MuÑoz LÓPEZ, C; COBOS SUÁREZ, P; MARTÍNEZ SAAVEDRA, G; SOLDEVILLA PUGA, C; DÍAZ LLORENTE, M (II Congreso Forestal Español, 1997)
This proyect intends both to reflect a synthesis of the results obtained in the study of the fungi related to Q. suber L., first in the Parque Natural de los Alcornocales (Cádiz), and then in other areas of Spain, and to highlight the rol of especific fungi detected in the group of all mycetes which are described in the same work
Keywords: Armillaria mellea; diplodia mutila; Hypoxylon mediterraneum; mycology flora; phytophthora cinnamomi; Quercus suber

PATOGENICIDAD DE HONGOS AISLADOS DEL ALCORNOQUE EN CATALUÑA - LUQUE, J; ÁLVAREZ, I (II Congreso Forestal Español, 1997)
Forty four fungal strains were used in pathogenicity tests made in trunk (32), leaves (8), and roots (8) of cork oak plants (Quereus suber L.) with two irrigation treatments (adequate and stress). Eleven species were found to be pathogenic on tnmk and three on leaf. Trunk pathogens such as Botryosphaeria stevensii, Phytophthora einnamomi, and (?)Diseula sp. caused the death of the inoculated plants. Hydric stress increased both canker and necrosis formation by (?)Diseula sp. and H. mediterraneum, reduced the effects of P. cinnamomi and had no effect on B. stevensii. The latter fungus was a virulent pathogen irrespectively of the irrigation treatment. Dendrophoma myriadea and (?)Fusieoeeum sp. were pathogenic on leaves. Both fungi were negatively affected by the hydric stress. However, no satisfactory results were obtained in the root inoculations. K.W.:
Keywords: Botryosphaeria stevensii; decline; Hypoxylon mediterraneum; pathogenic fungi; phytophthora cinnamomi; Quercus suber